Conselhos Municipais de Assistência Social e controle social - Jacqueline Oliveira da Silva (Universidade do Vale do Rio dos Sinos (UNISINOS), 2006)
This paper discusses the results of a case study research about councils of social assistance in the cities of São Leopoldo and Santo Antônio da Patrulha, RS, Brazil. Those cities were part of the national research City councils and social assistence and broadening of citizenship coordinated by UCPEL Catholic University of Pelotas and Brazilian Cáritas. The authors focus the discussion in the forms of social control made in such cities. They identify as well, through analysis of minutes and questionnaires that, when it comes to actions of social control, the difference of size of the cities is not substantial. The research results, in comparison to previous studies, indicate the need of revision of theory.